Occupational Burden of Chronic Obstructive Pulmonary Disease in the Commonwealth of Independent States: Systematic Review and Meta-Analysis - Vinnikov, Denis; Rybina, Tatsyana; Strizhakov, Leonid; Babanov, Sergey; Mukatova, Irina (Frontiers in Medicine, 2021)
Background. Population-based studies from Russian Federation and neighboring countries on the occupational burden of chronic obstructive pulmonary disease (COPD) are seldom or not included in the systematic reviews. The aim of this review was to summarize published population-based studies from the Commonwealth of Independent States (CIS) in order to ascertain the occupational burden of COPD. Methods. We systematically searched www.elibrary.ru and Pubmed for population-based studies on the epidemiology of COPD in nine countries using PRISMA. Quality of studies was assessed using the original tool. The odds of COPD in the included studies from vapors, dusts, gases or fumes (VDGF) was pooled using meta-analysis (fixed effects model), whereas the population attributable fraction percent (PAF%) was pooled with meta-proportion using random effects model in Stata 14.2. Results. Five studies, three from Russia, one from Kazakhstan and one more from Azerbaijan and Kazakhstan (total N=18908) with moderate to high quality and published from 2014 to 2019, none from Armenia, Belarus, Kyrgyzstan, Moldova, Tajikistan, and Uzbekistan, were included. Spirometry-defined COPD was the outcome in four of them. The pooled odds ratio (OR) of COPD from VGDF was 1.69 (95% confidence interval (CI) 1.34;2.13), greater in Kazakhstan (OR 1.96 (95% CI 1.35;2.85, N=2 studies)) compared to Russia (OR 1.52 (95% CI 1.13;2.05, N=2 studies)). The pooled PAF% was 6% (95% CI 2; 14%) from three studies. Conclusions. Population-based studies in the CIS get little attention with very few studies published. Although the effect was greater in Kazakhstan compared to Russia, the overall effect did not differ from studies published in the rest of the world. Research capacity to study occupational risks of COPD should be strengthened to produce more evidence of higher quality.